(untitled) (Journal of the College of Basic Education, 2019)
Aims research sought to acknowledge ( the effect of think – aloud strategy on the results of the fifth – grade students in the geography subject ) . In order to verify the objective of the research and its hypothesis , a sample of fifth grade students were selected in the city of Baghdad belonging to the general directorate of the Baghdad for the Secondary merning schools / Rasafa second district. Two groups of fifth – grade girls , both experimental and disciplined , were selected from the sumer girls secondary school , the study sample were 67 female students , 34 female students in the experimental group , and 33 students in the disciplined group ,Were the researcher did a equivalence in variables test ( age , academical achievement of the previous year in geography ) before doing the test and no statistical differences between the two groups were found . The results of the study showed that the students of the experimental group who studied natural geography using the " think – aloud " strategy was superior to the group of the elite and disciplined students when it came to the eligibility test .